The environmental crisis and African women’s displacements in War Girls by Tochi Onyebuchi - Ostalska, Katarzyna (Tydskrif vir letterkunde, 2025)
In the following article, I explore several types of dislocations (environmental, war, patriarchal, to name but a few) in Tochi Onyebuchi’s novel War Girls (2019), analysed from the methodological perspective of Africanfuturism. The aim of the article is to show how the second wave of African future-oriented literature (diasporic in this case) looks back to the past (the Nigerian Civil War) in order to seek solutions for the ongoing current problems, such as the devastation of the natural environment, climate change, the participation of underage soldiers in military conflicts, and new forms of capitalism and neolonialisation. The novel is read via historical, sociological, and frequently anthropological sources to demonstrate how the speculative discourse can be firmly grounded in the scientific context. Additionally, I propose a feminist and utopian reading of War Girls. The text is divided into parts where key elements of Africanfuturism—such as digitalisation, nanotechnologies, Information Technology, African cosmologies, and oral tradition—are discussed in detail and are shown as existing at the same time, entangled with the past and future simultaneously, within human and more-than-human worlds. Dans l’article suivant, j’explore plusieurs types de déplacements (environnementaux, liés à la guerre, patriarcaux, pour n’en citer que quelques-uns) dans le roman War Girls (2019) de Tochi Onyebuchi, analysés dans une perspective méthodologique afrofuturiste. L’objectif de cet article est de montrer comment la deuxième vague de littérature africaine tournée vers l’avenir (diasporique dans ce cas) se tourne vers le passé (la guerre civile nigériane) afin de trouver des solutions aux problèmes actuels, tels que la dégradation de l’environnement naturel, le changement climatique, la participation de soldats mineurs à des conflits militaires et les nouvelles formes de capitalisme et de néocolonialisme. Le roman est analysé à travers des sources historiques, sociologiques et souvent anthropologiques afin de démontrer comment le discours spéculatif peut être solidement ancré dans le contexte scientifique. De plus, je propose une lecture féministe et utopique de War Girls. Le texte est divisé en plusieurs parties où les éléments clés de l’afrofuturisme, tels que la numérisation, les nanotechnologies, les technologies de l’information, les cosmologies africaines et la tradition orale, sont discutés en détail et présentés comme coexistant, mêlés à la fois au passé et au futur, dans les mondes humains et plus qu’humains.